Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.3 - Integrated Review - Summary on Solving Quadratic Equations - Page 791: 12


$x_{1}=-\dfrac{3}{5} + \dfrac{\sqrt{6}i}{5}$ and $x=-\dfrac{3}{5} - \dfrac{\sqrt{6}i}{5}$

Work Step by Step

Given $5x^2+6x=-3 \longrightarrow 5x^2+6x+3=0$ $a= 5, \ b=6, \ c=3$ Using the quadratic formula: $\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}$ we have: $\dfrac{-6\pm \sqrt{6^2-4\times 5\times 3}}{2 \times 5} = \dfrac{-6\pm \sqrt{36-60}}{10} = \dfrac{-6\pm \sqrt{-24}}{10} = \dfrac{-6\pm \sqrt{4\times (-6)}}{10} = \dfrac{-6\pm 2\sqrt{-6}}{10} =\dfrac{-3\pm \sqrt{-6}}{5} =\dfrac{-3\pm \sqrt{6}i}{5} =\dfrac{-3}{5} \pm \dfrac{\sqrt{6}i}{5}$ Therefore the solutions are $x_{1}=-\dfrac{3}{5} + \dfrac{\sqrt{6}i}{5}$ and $x=-\dfrac{3}{5} - \dfrac{\sqrt{6}i}{5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.